Is There a Need for Early Palliative Care in Patients With Life-Limiting Illnesses? Interview Study With Patients About Experienced Care Needs From Diagnosis Onward. (June 2016) - Beernaert, Kim; Deliens, Luc; De Vleminck, Aline; Devroey, Dirk; Pardon, Koen; Block, Lieve Van den; Cohen, Joachim
The early integration of specialist palliative care has been shown to benefit the quality of life of patients with advanced cancer. In order to explore whether other seriously ill people and people at even earlier phases would also benefit from early palliative care, we conducted 18 qualitative interviews with people having cancer, chronic obstructive lung disease, heart failure, or dementia at different phases of the illness trajectory about how they experienced care needs related to their disease from diagnosis onward. Respondents experienced needs within the different domains of palliative care at different stages of the illness and different illness types or duration of the illness. This study contributes to the understanding of primary care needs of patients for whom palliative care (not necessarily specialized palliative care) could be beneficial.